WACANA CIVIL SOCIETY (MASYARKAT MADANI) DI INDONESIA - Masroer Jb; Lalu Darmawan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This article describes the concept of civil society, which is more popular among the Muslims as Madani Society. The position of civil society is construct by the formation of various social institutions, particularly the non-government organizations. Non-Government Organization, which has autonomy and control of process’s government activities, is essential for the creation of Madani Society. Pluralism, Freedom of speech and expression, and control’s function are the important elements of democracy. It is apparent that there is a close connection between democracy and civil society. There will be no democracy without the development of civil society.